Methodological guide in English for elementary school "My cheerful ABC" - Sereda I. N. (SCC "Interactive plus", LLC, 2023)
The manual is intended for elementary school students and teachers. It will help them in a playful way to learn phonetic, lexical and grammatical material when learning English.
Keywords: лексика; фонетика; грамматика; vocabulary; Grammar; phonetics